Pike County Ballads and Other Poems - Hay, John, 1838-1905 (Salt Lake City, UT : Project Gutenberg, 2004)
"Pike County Ballads and Other Poems" by John Hay is a collection of poems written in the late 19th century that vividly captures the spirit and culture of rural America, particularly in the Midwest. The work showcases a diverse array of poetic styles, weaving together narratives that celebrate both the rugged lives of its characters and the broader themes of humanity, love, and struggle. Set against the backdrop of American history, the poems reflect a deep connection to the land and its people, drawing upon folk traditions and personal experiences. The opening of the collection introduces readers to a variety of stories and characters, beginning with the tale of Jim Bludso, an engineer on the "Prairie Belle," who heroically sacrifices himself to save others from a burning steamboat. This is followed by the touching story of "Little Breeches," a father$1 (Bs expression of love and faith when he finds his child miraculously safe after a terrifying loss. Other narratives, like "Banty Tim," highlight themes of loyalty and courage, especially in the context of race and the Civil War, demonstrating Hay's engagement with complex social issues of his time. Through these early poems, Hay paints a vibrant picture of a frontier life filled with rich characters, moral dilemmas, and poignant relationships, setting the tone for the rest of the collection. (This is an automatically generated summary.)s
Wikipedia page about this book: https://en.wikipedia.org/wiki/Pike_County_Ballads
Release date is 2004-07-01
Produced by Les Bowler and David Widger
Keywords: American poetry -- 19th century; Ballads, English -- United States